Análise e simulação do processo de transporte de biometano via bio-GNC e bio-GNL - Santos, Hyago Braga dos (2022)
The present work aimed to carry out the modeling of the biomethane transport stage in Brazil by bioCNG and bioLNG modals, in order to determine the radius of action of each modal in the implementation of a system of virtual pipelines, aiming at the minimization of the costs involved in the studied process. Through the optimization of the proposed model in a Python programming environment, it was observed that the bioCNG modal is favored over shorter distances and with lower daily demands. For the developed model, sensitivity analysis studies were carried out involving variables such as average transport speed, CAPEX and OPEX costs, acquisition value of trailers and trucks, and internal rate of return, so the average speed of trucks proved to be a variable of great impact on the choice of modal, for which lower speed scenarios the bioLNG modal was benefited in relation to the bioCNG modal. In general, the results obtained through the simulation of the process were congruent with the real values, and for the demand scenario of 6000m³/day and displacement of 700km, the transport cost was 1.59R$/m³, 0.02R$/m³ lower than the real values, indicating errors of less than 2% of the values spent by the company GEO Biogas&Tech, showing the accuracy of the model developed in view of the considerations taken for the comparison. Thus, based on the validation of the model, it is possible to use it by decision makers to assist in choosing the best modal for the transport of biomethane through virtual pipelines constituted by bioCNG and bioLNG.